PERANCANGAN DESIGN WEBSITE DAN APLIKASI PLATFROM PODCAST “SOUNDS” GUNA MENINGKATKAN KUALITAS TAMPILAN DAN DAYA TARIK USER DI PT MEDIA TELEVISI INDONESIA - Nurnissa Nissa Maharani (Jurnal Media Infotama, 2023)
At this time, podcasts have become a trend in Indonesia. Many content creators to influencers create content based on radio broadcasts or commonly known as podcasts. The audience feels interested in this content because there is an interesting discussion process that is presented in a relaxed manner. Podcast is one of the content media that has received a lot of public attention. Because it seems more flexible and intense when compared to radio broadcasts in general. For example CBC Radio One, Pod.me, BBC and so on. At this time, it's not only the big broadcasting media that can host podcasts, but you can be one of the people who can host podcasts. Based on the above problems, the solution is to design a UI/UX application and a podcast platform website called SOUNDS using Human Centered HCD Design. HCD is an approach that focuses on all potential users of information systems or not being the object of trials in the data collection process and evaluation process on website information systems that are being designed to create the SOUNDS podcast platform to improve display quality and user attractiveness. Keywords : Podcast, Strategi:Human Centered Design (HCD), UI/UX Design